Thermo-economic analysis of a Coal-Fired Power Plant (CFPP) using turbine cycle heat rate and plant net heat rates at various operating loads - Singh, Manmit Singh Jasbeer; Abdul Jalil, Nawal Aswan; Abdul Rahim, Sharafiz; Zulkefli, Zamir Aimaduddin; Hasini, Hasril (Universiti Putra Malaysia Press, 2022)
Evaluating Coal-Fired Power Plant (CFPP) performance is a complex process involving the determination of the turbine cycle Heat Rate (TCHR). This study focuses on determining the TCHR by developing a mathematical model. The model, which incorporates economic analysis of the plant, is developed using energy and mass balance relationships of the turbine cycle, validated using plant commissioning data from a 700MWn CFPP located in Perak, Malaysia. Actual plant data from a 700MWn CFPP is utilized to improve the accuracy and increase the confidence of the results of this study. It was found that at the nominal operating load of 729MWg, there is a Heat Rate (HR) deviation of -1,135 kJ/kWh, leading to daily losses of RM240,447 or USD 60,112. Furthermore, it is possible to utilize the developed model at lower loads as the plant is now being used to operate on “cyclic” loads. The daily losses at a lower load of 431MWg are RM125,767 or USD31,442. Thus, the model is able to compare the plant HR at various loads against commissioning data, and economic analysis is able to be carried out effectively. Valuable information for plant operations and performance engineers could be obtained using this model to determine plant HR.